Does Project Management Information System Influence the Operational Performance of Public Information Systems Departments in the Moroccan Public Sector? - Mustapha Bindguigne; Mohamed Akhlaffou; Salka Akhlaffou (Proceedings of The International Conference on Research in Management and Economics, 2026)
The operational performance of the Information System Departments (ISDs) of Moroccan Ministries is central to the effectiveness and efficiency of digitalized public services. Based on this premise, the Project Management Information System (PMIS) emerges as a key tool for optimizing the planning, execution, and evaluation of IT projects within public ISDs. This conceptual study explores the theoretical framework linking PMIS to operational performance in public ISDs, highlighting the role of this system in the overall success of IT projects. Through a synthetic review of project management literature and public-sector IT governance frameworks, we examine how PMIS contributes to evaluating operational performance through specific indicators such as project delivery time, budget adherence, resource utilization, and stakeholder satisfaction. Our analysis reveals that PMIS enhances performance primarily through improved coordination mechanisms, real-time monitoring capabilities, and data-driven decision-making processes. The study also identifies implementation challenges, including integration complexity, resistance to change, and data security concerns. We conclude that successful PMIS adoption in Moroccan public ISDs requires a phased implementation approach, stakeholder engagement strategies, and robust training programs, recommendations that offer practical guidance for public-sector digital transformation initiatives.